An Introduction to the Ethics of Gestalt Research with informants - Krüger, Ashild (European Journal for Qualitative Research in Psychotherapy, 2007)
The fact that Gestalt qualitative research, based on holistic thinking, is seen as an intersubjective process between researcher and informant raises the ethical question of how the researcher deals with the dilemma of inherent positional power. According to the ethics of interrelations, the term “conscious, ethical use of power” is suggested to highlight central aspects of the ethical responsibility of the researcher at work. In fact, this responsibility constitutes a moral obligation in all phases of the research process.Although the aims of Gestalt therapy and those of Gestalt research are different, their ethical challenges are similar, not least when it comes to the question of dealing with the imbalance of positional power in a professionally defined relationship.Based on holistic thinking, Gestalt qualitative research considers the interaction between researcher and informant to be a unified field of interactive subjects, fundamentally the same structures found in therapy. In most cases the informant even becomes a co-researcher in active dialogue with the investigator and accordingly, the two are co-creators at least in parts of the research process (Barber, 2002; Reason, 1988).However, in this field of co-researchers, the professional inquirer is, whether he or she likes it or not, in a superior position. First of all the researcher is associated with the academic institution, which in itself in our Western World means authority. This authority is frequently reinforced when common sense observations from the informant are presented in academic theories, using a language which may not be easily understandable by people without the needed code for interpretation.Secondly, the researcher has the upper hand simply because of being fully informed about the purpose of the investigation. As a matter of fact, due to this superior position, the researcher runs the risk of exploiting the other: in a qualitative interview the objective is to get as much information for data collection as possible and consequently, the interviews with the informants are conducted in order to have them tell as much as possible about their experience with a certain phenomenon. Moreover, being in control of the interview procedures, the researcher is the one who through certain techniques not only has the power to open up to experiences but also to close them off - again, always on the outlook for the best possible data for his research.Throughout the article I will accompany my reflections with examples from practice: anonymous stories from my own and my colleagues’ experiences as informants or researchers. Let us start with an illustration of how the inquirer’s position as a knower is in a subtle way omnipresent in research:Ann is an excellent informant because she talks freely about the sensitive theme of sorrow and shame. She works as a cleaning woman, and is not familiar with the academic world. She is invited to a qualitative interview to share her experience after the death of her son, who committed suicide three years ago. Apparently, during the conversation all went well, but in reviewing the transcript the researcher became aware of a critical point as the informant’s vulnerability had been revealed because he had not fully informed her about the emotional consequences of opening up to the traumatic experience.In this case, the investigator is definitely confronted with basic ethical issues. First, the example shows that the researcher is the knower who definitely is more informed than Ann. Secondly, and even worse, it seems that the researcher at a certain moment is not aware of the position as a knower, or realising the problem too late.In my opinion the field between informant and researcher – illustrated in the account above – will inevitably be characterised by an imbalance of power, an imbalance which in Gestalt terms influences the field between ethically equal subjects (Yontef & Simkin, 1989). Therefore, as power is intrinsic in the researcher’s position, the question is how to make the impact of power as little harmless to the informant as possible – which in turn further leads to the basic question: How is it possible to behave ethically in a position of power? To answer this we first need to look at theory in short, using previous analyses of ethics in relationships.